WHEAT SEED (TRITICUM AESTIVUM L.) RADIOCARBON CONCENTRATION OVER THE LAST 75 YEARS. Issue 5 (30th October 2021) - Hüls, C Matthias; Börner, Andreas; Hamann, Christian
ABSTRACT: Here we report radiocarbon measurements made on wheat seed tissue ( Triticum aestivum L.; winter or spring type growth habit), from the seed archive of the IPK Gatersleben, Sachsen-Anhalt, Germany, which was harvested between 1946 and 2020. The results give an overview of 75 years of radiocarbon concentration evolution in agricultural plant products. The wheat tissue radiocarbon concentrations follow known pre- and post-bomb radiocarbon records, such as the atmospheric Jungfraujoch, Schauinsland, and NH1 datasets. Based on a Northern Hemisphere growing period from April to July, the Gatersleben seed tissue radiocarbon concentration indicates incorporation of fossil carbon of about 1% with respect to the high alpine, clean-air CO2 of the Jungfraujoch station between 1987 and 2019. We propose to use the pre- and post-bomb radiocarbon record of Gatersleben wheat as a reference in forensic investigations, such as the age estimation of paper by analyzing starch used in paper manufacture. Additionally, an advantage of the record reported here lies in its extensibility by adding new analyses from future harvests.